THE CORRELATION BETWEEN LEARNING STYLES AND SELF-CONFIDENCE ON STUDENTS' MOTIVATION AT SMK PERIKANAN PROVINSI RIAU - ANJANI, ELLA NOVI (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research was aimed at finding out the correlation between learning styles and self-confidence on student’s motivation At SMK Perikanan Provinsi Riau. This research was a correlational study using quantitative method. The subject of the research was all students of SMK Perikanan Provinsi Riau consisting 10 classes. The research sample was taken by using random sampling method from ten classes which each class has different number of students. The total population was 227, and the total sample was 114. The data was analyzed by using SPSS version 17. Based on the descriptive statistic of learning styles showed that group was the favorite styles who has chosen by student at Smk Perikanan Provinsi riau with mean score 18.64, another favorite styles was kinesthetic with means score 15.49. Furthermore, the total students who have high self-confidence were 80 persons and 34 students for average score. Additionally, students who have medium level were 69, 30 students for high level and 15 students for low level. The research findings showed that first; there was no significant correlation between learning styles and student’s motivation with score 0.18>0.05. Second, there was significant correlation between self-confidence and student’s motivation with score 0.00< 0.05. Third, there was significant correlation between learning styles and self-confidence on student’s motivation with score 0.00<0.05 at Smk Perikanan Provinsi Riau. Keyword : Learning Styles, Self-Confidence, Student’s Motivation